2021
DOI: 10.7759/cureus.15141
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucagon-Like Peptide-1 Receptor Agonists in the Management of Non-Alcoholic Steatohepatitis: A Clinical Review Article

Abstract: Non-alcoholic fatty liver disease (NAFLD) has emerged as one of the lethal causes of chronic liver disease globally. NAFLD can ultimately progress to non-alcoholic steatohepatitis (NASH) given persistent cellular insult. The crux of the problem lies in fat accumulation in the liver, such as increased fatty acid substrates owing to consumption of a high-fat diet, altered gut physiology, and excess adipose tissue. Being the hepatic manifestation of metabolic syndrome, insulin resistance is also among one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a randomized controlled clinical trial, exenatide clearly reduced liver fat content in patients with drug-naïve T2DM and NAFLD, and led to greater reductions of body weight, visceral fat, and liver enzymes than insulin glargine ( Liu L. et al, 2020 ). Several studies have shown that exenatide has a predominant role in reducing ALT levels, thereby promoting weight loss, inhibiting inflammation to some extent, and preventing deterioration of steatosis ( Ghazanfar et al, 2021 ). Exenatide may be incorporated into streamlined individualized therapy for NAFLD.…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…In a randomized controlled clinical trial, exenatide clearly reduced liver fat content in patients with drug-naïve T2DM and NAFLD, and led to greater reductions of body weight, visceral fat, and liver enzymes than insulin glargine ( Liu L. et al, 2020 ). Several studies have shown that exenatide has a predominant role in reducing ALT levels, thereby promoting weight loss, inhibiting inflammation to some extent, and preventing deterioration of steatosis ( Ghazanfar et al, 2021 ). Exenatide may be incorporated into streamlined individualized therapy for NAFLD.…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…GLP-1 has a very short half-life in vivo, and is degraded by dipeptidyl peptidase-4 (DPP-4), so it cannot be used for disease treatment. 184 GLP-1 RA belongs is an incretin drug with pleiotropic effects such as lowering blood glucose and blood lipids and reducing body weight. 185 Recent studies have found that GLP-1 RA improved IR in NAFLD, reduced liver steatosis, and improved liver fibrosis.…”
Section: Glucagon-like Peptide-1 (Glp-1) Receptor Agonists (Glp-1 Ras...mentioning
confidence: 99%
“…Furthermore, exenatide demonstrated an ability to decrease the lipid content and inflammation in the liver of APOE*3-Leiden.CETP mice by inhibiting the expression of liver chemokines and the gathering of oxLDL in macrophages [ 152 ]. GLP-1 RAs activity on both hepatic and adipose tissue, which is linked with suppressed expression of pro-inflammatory mediators, such as cytokines (e.g., IL-6 and TNF-a) and chemokines (e.g., monocyte chemoattractant protein-1 (MCP-1), vascular cell adhesion molecule (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin), is fundamental in regulating fibrosis in NASH [ 153 , 154 ]. Moreover, this downregulation, along with an inhibition of macrophage infiltration, plays an important role in enhancing insulin sensitivity.…”
Section: Explaining the Effectiveness Of Incretin-based Drugs On Nash...mentioning
confidence: 99%